IMPLEMENTASI STRATEGI PEMBELAJARAN BERBASIS INQUIRY DALAM PELAKSANAAN PRAKTIKUM BIOLOGI TERAPAN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MAHASISWA DI PROGRAM STUDI PENDIDIKAN BIOLOGI - Sri Wulandari (Program Studi Pendidikan Biologi, 2014)
Action research has been conducted with the implementation of inquiry - based learning strategies in the implementation of applied biology laboratory activity and to improve student learning outcomes . The experiment was conducted in the second semester of academic year 2012/2013 in the Biology Faculty of Teacher education Program UR . Subjects were students take courses in Applied Biology with a number of 52 students ( 10 men and 42 women ) . Parameters measured were activities in practicum and student learning outcomes . The study consisted of 2 cycles with 6 meetings . The data were analyzed descriptively . The results show there is an increase in activity and student learning outcomes from the first cycle to the second cycle . Student activity in cycle 1 : submit ideas , doing experiments , working together , observations classified as category very well , whereas hypothesize , ask and make conclusions either classified category . While on cycle 2 activity categories well and asking other classified categories classified as very good . Learning outcomes in cycle 1 is very good very good category 17 students ( 32.69 % ) and second cycle increased to 31 students ( 59.61 % ) . Overall the implementation of inquiry -based learning can enhance the activity and student learning outcomes in the practicum course in the second semester of Applied Biology academic year 2012/2013 in Biology Education Riau University.Keywords : Botany , inquiry